Teaching Implication of Meaning Construction at Morphological Level of Affixation in a Complex Indonesian Verb Formation - Sudana, Dadang; Hardini, Tri Indri; Zifana, Mahardhika (Universitas Negeri Makassar, 2024)
A tension exists between rationalists and empiricists regarding the nature of knowledge: innate then activated/discovered (rationalists) or constructed then invented (empiricists). The assumption is that, to a certain extent, basic knowledge seems to be innate in our mind and develops through experience by thinking processes to construct meanings. This meaning construction (thinking), mainly using language, is to make sense of and interpret the world. Meanings should be the primary motivation underlying linguistic constructions at all levels. This paper investigates meaning constructions at the lexical level of affixation by focusing on semantic behaviours of verbs in a complex word formation as an attempt: 1) to find out the semantic patterns of verb-based complex word formation, 2) to reveal if there is an iconic relationship of a sign (signifier) and its meaning (signified), and 3) to suggest for its teaching. Using semantic classes of verbs, based on situation types in deriving complex words, this study attempts to find out semantic patterns of such complex word formation and the possibility of revealing its iconicity. Using Antconc software, this study scrutinized linguistic expressions involving related verbs of state, event, and action in a corpus to reveal meaning construction at that level. The findings show several semantic patterns of verb-based complex word formation and an indication of the iconicity of signs. The paper also offers suggestions for teaching affixation